Formation of the synaptonemal complex in a gynogenetic allodiploid hybrid fish - Wang, Jing; Wang, Wen; Li, Jihong; Zhang, Yirui; Luo, Kaikun; Han, Linmei; Xiang, Caixia; Chai, Mingli; Luo, Ziye; Zhao, Rurong; Liu, Shaojun (Frontiers in Genetics, 2023)
Introduction: The correct pairing and separation of homologous chromosomes during meiosis is crucial to ensure both genetic stability and genetic diversity within species. In allodiploid organisms, synapsis often fails, leading to sterility. However, a gynogenetic allodiploid hybrid clone line (GDH), derived by crossing red crucian carp (Carassius auratus ♀) and common carp (Cyprinus carpio ♂), stably produces diploid eggs. Because the GDH line carries 100 chromosomes with 50 chromosomes from the red crucian carp (RCC; ♀, 2n = 2x = 100) and 50 chromosomes from the common carp (CC; C. carpio L., ♂, 2n = 2x = 100), it is interesting to study the mechanisms of homologous chromosome pairing during meiosis in GDH individuals. Methods: By using fluorescence in situ hybridization (FISH) with a probe specific to the red crucian carp to label homologous chromosomes, we identified the synaptonemal complex via immunofluorescence assay of synaptonemal complex protein 3 (SCP3). Results: FISH results indicated that, during early ovarian development, the GDH oogonium had two sets of chromosomes with only one set from Carassius auratus, leading to the failure formation of normal bivalents and the subsequently blocking of meiosis. This inhibition lasted at least 5 months. After this long period of inhibition, pairs of germ cells fused, doubling the chromosomes such that the oocyte contained two sets of chromosomes from each parent. After chromosome doubling at 10 months old, homologous chromosomes and the synaptonemal complex were identified. Discussion: Causally, meiosis proceeded normally and eventually formed diploid germ cells. These results further clarify the mechanisms by which meiosis proceeds in hybrids.